The Power of Gaze in Music. Leonard Bernstein’s Conducting Eyes - Isabella Poggi; Loredana Ranieri; Ylenia Leone; Alessandro Ansani (Multimodal Technologies and Interaction, 2020)
The paper argues for the importance and richness of gaze communication during orchestra and choir conduction, and presents three studies on this issue. First, an interview with five choir and orchestra conductors reveals that they are not so deeply aware of the potentialities of gaze to convey indications in music performance. A conductor who was utterly conscious of the importance of gaze communication, however, is Leonard Bernstein, who conducted a performance of Haydn’s Symphony No. 88 using his face and gaze only. Therefore, a fragment of this performance is analyzed in an observational study, where a qualitative analysis singles out the items of gaze exploited by Bernstein and their corresponding meanings. Finally, a perception study is presented in which three of these items are submitted to expert, non-expert, and amateur participants. The results show that while the signal for “start” is fairly recognized, the other two, “pay attention” and “crescendo and accelerando” are more difficult to interpret. Furthermore, significant differences in gaze item recognition emerge among participants: experts not only recognize them more, but they also take advantage of viewing the items with audio-visual vs. video-only presentation, while non-experts do not take advantage of audio in their recognition.